PERAN LEMBAGA PENDIDIKAN PRA-NIKAH DALAM PENCEGAHAN TINGGINYA KHULU’ PADA RUMAH TANGGA ISLAM ( Studi Kasus Pada Lembaga Pendidikan Pra-Nikah di Kota Malang: Klinik Nikah ) - Zahrah Salsabila; Khoirul Asfiyak; Moh. Muslim (Jurnal Hikmatina, 2022)
Khulu's divorce during the COVID-19 pandemic in Malang City is very increased. The main cause of lack of communication, and constant disputes. Therefore, it is recommended to take pre-marital education. Divorce is common, from time to time and this issue turns into an interesting issue to observe. Therefore, it is important to have a pre-wedding educational institution to provide education for prospective brides. The observed method usedIs quantitative. This is part of this field research strategy or case studyThe subjects were the Malang Marriage Clinic Education Institute employees and 5 alumni of the institution. Data is obtained by using data reduction, data presentation, and drawing conclusions or verification during the observation. The results of this observation indicate that the COVID-19 pandemic impacts divorce due to abnormal family and continuing differences of opinion. Keywords: Pandemic Covid-19, Divorce, Khulu’, Marriage Clinic Education